Factors associated with acquisition and retention of costumers in supply chain services - Γεωργιάδου, Ιφιγένεια; Georgiadou, Ifigeneia (2021)
The thesis consists of two parts. The first part refers to the literature review of the terms supply chain management and services, costumer acquisition and retention. Second part concerns the survey that has been conducted, the methodology that has been applied and the analysis of results. Particularly, the followed approach comprises four steps. First the related literature is reviewed to acquire a good understanding regarding customer acquisition and retention in supply chain services. Second step is related with the collection of data, which has been realized by distributing questionnaires (September-October 2016), mostly in Greek companies asking for information about the factors that lead them choose and retain their suppliers. Next, the collected data have been analyzed both according to the descriptive statistics they provided and mainly with the use of Factor Analysis (FA) method. Finally, the divergent firm types towards suppliers’ acquisition and retention are determined leading to the drawing of final conclusions. Moreover, the results with companies' preferences are analytically presented. The thesis includes original work based on primary data from survey. The results are important for companies within supply chains who desire creating long terms relationships with their customers or acquire new ones. In addition, the results might be useful for marketing interested parties.